DISCOVERING THE BEAUTY AND FORTITUDE OF KASHMIRI CULTURE AND CUSTOMS - Shabir Ahmad Dar; Irfan Ahmad Mir (RADJA PUBLIKA, 2023)
Abstract The cultural tapestry and customs of Kashmir form a diverse and intricate montage shaped over the course of centuries. Situated in the northernmost reaches of India, Kashmir's evolution has been molded by a multitude of cultures and faiths, resulting in a distinctive fusion of rituals and ways of life. The inhabitants of Kashmir are renowned for their gracious reception, intricate craftsmanship, delectable gastronomy, and melodic expressions of music and dance, all emblematic of their ancestral lineage. Notwithstanding its allure and opulence, Kashmir's cultural ethos has encountered adversities such as conflict, displacement, and environmental degradation. Despite these trials, the resilience of Kashmiri culture and its traditions has endured, forging ahead with vigor. Through an exploration of the distinctive customs and rituals of the Kashmiri populace, this exposition seeks to underscore the splendor and opulence inherent in their cultural legacy, emphasizing the imperative of safeguarding it for generations yet to come